The Omo-Kibish I pelvis. Issue 108 (July 2017) - Hammond, Ashley S.; Royer, Danielle F.; Fleagle, John G.
Abstract: Omo-Kibish I (Omo I) from southern Ethiopia is the oldest anatomically modern Homo sapiens skeleton currently known (196 ± 5 ka). A partial hipbone (os coxae) of Omo I was recovered more than 30 years after the first portion of the skeleton was recovered, a find which is significant because human pelves can be informative about an individual's sex, age-at-death, body size, obstetrics and parturition, and trunk morphology. Recent human pelves are distinct from earlier Pleistocene Homo spp. pelves because they are mediolaterally narrower in bispinous breadth, have more vertically oriented ilia, lack a well-developed iliac pillar, and have distinct pubic morphology. The pelvis of Omo I provides an opportunity to test whether the earliest modern humans had the pelvic morphology characteristic of modern humans today and to shed light onto the paleobiology of the earliest humans. Here, we formally describe the preservation and morphology of the Omo I hipbone, and quantitatively and qualitatively compare the hipbone to recent humans and relevant fossil Homo . The Omo I hipbone is modern human in appearance, displaying a moderate iliac tubercle (suggesting a reduced iliac pillar) and an ilium that is not as laterally flaring as earlier Homo . Among those examined in this study, the Omo I ischium is most similar in shape to (but substantially larger than) that of recent Sudanese people. Omo I has features that suggest this skeleton belonged to a female. The stature estimates in this study were derived from multiple bones from the upper and lower part of the body, and suggest that there may be differences in the upper and lower limb proportions of the earliest modern humans compared to recent humans. The large size and robusticity of the Omo I pelvis is in agreement with other studies that have found that modern human reduction in postcranial robusticity occurred later in our evolutionary history.